Perfil epidemiológico e fatores associados em indivíduos com impacto femoroacetabular - Marek, Alexandre (2019)
The hip joint is a spherical joint that allows a great deal of movement, consisting of the acetabular fossa of the iliac bone and the femoral head. Because it is a very mobile joint, it is susceptible to some pathologies such as femoroacetabular impact. Evidence suggests that femoroacetabular impact plays an important mechanical role in the development of hip arthrosis, as all coxarthroses without apparent cause are believed to be secondary to previously underestimated or unrecognized acetabular and femoral changes. Alternatively, video arthroscopy aims to alleviate symptoms and improve hip range of motion impacted by the pathology. In this sense, the objective of this study was to verify the epidemiological profile and associated factors in individuals affected by femoroacetabular impact. This was a retrospective and descriptive cross-sectional study, which evaluated the medical records of individuals seen at the Hip Surgery Service of the Institute of Orthopedics and Traumatology, in the city of Passo Fundo / RS, between January 2016 and July 2018. Sociodemographic and clinical records were collected, such as gender, laterality, type of femoroacetabular impact and presence of labral lesion, chondral lesion and / or hip osteoarthrosis. Afterwards, the data were analyzed using descriptive statistics. In all, 209 hips (of 179 individuals) were affected by femoroacetabular impact, 126 males (60.28%), and 39 females (39.72%). In men, the prevalence of femoroacetabular impact was 42.99% on the left side (44), 38.32% on the right side (41) and 18.69% bilateral (20). In women, the prevalence of femoroacetabular impact was 47.22% on the left side (34), 38.89% on the right side (28) and 13.89% bilateral (10). Regarding the types of femoroacetabular impact, men presented 71.96% mixed type (77), 17.75% Came type (19) and 10.28% Pincer type (11), while women presented 69, 44% the mixed type (50), 27.77% the Cam type (20) and 2.77% the Pincer type (2). Still, 46.88% of the hips presented labral lesion (98), 30.14% presented chondral lesion (63) and 6.69% osteoarthritis (14). The individuals with femoroacetabular impact who underwent hip video arthroscopy are mostly men, with the left side affected and with mixed femoroacetabular impact. Although most of the hips do not present associated injuries, among the investigated ones, labral lesions, chondral lesions and osteoarthritis, respectively, stand out.